AGE-SPECIFIC ACUTE CHANGES IN CAROTID-FEMORAL PULSE WAVE VELOCITY DURING HEAD-UP TILTING. (April 2021) - Pucci, Giacomo; Avolio, Alberto; Spronk, Bart; Tap, Lisanne; Vaudo, Gaetano; Anastasio, Fabio; Van De Meiracker, Anton; Mattace-Raso, Francesco
Abstract : Objective: Hydrostatic blood pressure (BP) gradient following changes in body posture may generate concomitant, age-dependent, increases in aortic stiffness. We analyzed the relationship between BP gradient, measured during head-up body tilting, and related changes in carotid-femoral pulse wave velocity (cf-PWV) at different age ranges, with the aim to separate the BP-dependent and BP-independent components of cf-PWV. Design and method: cf-PWV and other hemodynamic parameters were measured in 30 healthy individuals during head-up tilting at 0°, 30° and 60°. BP was taken at the upper arm, constantly kept at heart level. Aortic BP was reconstructed from radial tonometry (SphygmoCor). Stiffness index β0 was estimated at 0° (Spronck et al, J Hypertens 2017;35:98–104). We assumed that: from MRI studies (Sugawara et al, Am J Hypertens. 2016;29:1237–1244), the effective cf-PWV travel distance (ETD, 80% of straight carotid-to-femoral distance) begins at heart level; the change in DBP along the aorta is predictable from the hydrostatic pressure gradient (0.73 mmHg/cm, Gavish et al, J Hypertens. 2011;29:2099–2104); cf-PWV and hydrostatic pressure relate linearly, hence predicted cf-PWV can be calculated as the average of aortic (using β0 and aortic DBP) and femoral (using β0 and femoral DBP, corresponding to aortic DBP + (ETD x sin(α)*0.73)) PWVs. Results: cf-PWV and peripheral SBP increases during head-up body tilting were different between age groups, being more pronounced in the "old" (>45 years) vs "young" group (both p for interaction <0.05), whereas both central and peripheral DBP changes were not influenced by age (Figure, panel left). Central SBP was not affected by tilt angles. When cf-PWV gradient measured by applanation tonometry (observed), was compared with that predicted from estimated DBP gradient (predicted), the difference in observed-vs-predicted PWV gradient increased non-linearly as a function of age (R2 for quadratic trend=0.38, p < 0.01, p vs linear=0.04, Figure panel right). Figure. No caption available. Conclusions: Under a hydrostatic pressor gradient, the pulse wave travelling along the aorta undergoes positive acceleration which, for any given pressor change, increases non-linearly as a function of age. The evaluation of aortic pulse wave acceleration induced by pressor gradient may be of clinical relevance as a marker of vascular ageing.